Fraseologia dell’algherese: risorse e nuovi impulsi per la fraseografia e la fraseodidattica di una varietà linguistica minoritaria italiana - Autelli, Erica; Caria, Marco (Linguistik Online, 2022)
The Catalan of Alghero is poorly documented at a lexicographic level, and the number of phrasemes to be found in the dictionaries is small. So, where can such word combinations be found and how can they be included in dictionaries? The present article aims to answer these two questions, giving a first overview of the phraseography of diatopic varieties in Italy, followed by information on Algherese and the description of possible resources from which the relevant information could be drawn. This is followed by a sociolinguistic investigation showing the complexity of the topic and a few divergencies from Italian, of which one should take account in the phraseodidactics of Algherese.